Evaluation of groundwater supply potential from hydraulic parameters estimated from vertical electrical sounding (VES) in Ikeduru, south east Nigeria - Jacinta Chiemela, Nwosu; I Nwosu, Leonard; O Chukwu, Godwin (International Journal of Advanced Geosciences, 2019)
A Vertical Electrical resistivity Sounding (VES) survey was carried out, to study the groundwater supply potential, protective capacity and soil corrosivity of aquifers in Ikeduru Local Government Area of Imo state, Nigeria. A total of ten (10) geoelectric soundings were acquired. Schlumberger electrode configuration was used in acquiring the data. Six to seven geoelectric layers were delineated from the interpreted results, the Aquifers were delineated between the fifth and sixth geoelectric layers, having an apparent resistivity above 1000Ωm, with the highest thick of 69.0m at a depth of 144.0m. Longitudinal Conductance, Hydraulic Conductivity, Transmissivity and Product Conductance range are as followings for the aquifers; 1.720 – 127.000 x 10-3Ω-1, 15.90 – 188.79m/day, 1093.3 – 1097.1m2/day and 2.590 – 252.50 x 10-3 respectively. Inferring from our hydraulic parameters, all the aquiferous zones have very high designation, wwithdrawal of great regional importance of groundwater supply potential and practically noncorrosive, soil corrosivity. 40% percentage of the aquiferous units have very good protective capacity, while for excellent and good protective capacity of the study are is 30%. All the VES points are said to be a very viable potential for safe source for groundwater exploration.